92 Relocation in Care Homes (RICH) Study: The Experience of Different Stakeholders. (6th February 2020) - Baron, S; Bridges, J; McGrath, N; Roberts, H C; Ibrahim, K
Abstract: Introduction: In the UK, care homes in unsuitable older buildings are closing. Involuntary relocation is associated with increased mortality and negative emotions among residents. Extensive planning can mitigate this. The aim was to understand the experience of a planned relocation between two care homes. Methods: In the UK, care homes in unsuitable older buildings are closing. Involuntary relocation is associated with increased mortality and negative emotions among residents. Extensive planning can mitigate this. The aim was to understand the experience of a planned relocation between two care homes. Results: Seven themes were identified and organised under three stages: pre-move (communication and involvement; preparation for the move; and attitudes towards the move), day-of-the-move (organisation of the move), and post-move (environmental change and impact; staff organisation and management; and settling in). Family and staff members reported that the pre-move information provided was inconsistent and staff did not feel involved in the planning and design process. Pre-move visits and staff and family support were beneficial for residents' preparation for the move. All participants expressed sadness about the closure, and reported apprehension about moving. The moving day felt disorganised and stressful to staff who had to spread between the two homes. Post-move, the new care home was perceived by many participants as a 'hotel' rather than a home. Its larger size and confusing layout impacted negatively on residents and staff. New staff and changes in management structure were perceived by the different stakeholders to cause increased staff workload. Residents adjusted variably to the new home, with family support and staff continuity of care proving to be facilitators. Conclusions: Despite extensive planning, relocation and adjustment was challenging. Recommendations for future relocations include: increasing involvement of staff in the planning and design of the home; ensuring consistent communication and organising staff rotas to maintain continuity of care.